Assessing least-cost mitigation methods for environmental phosphorus loading of different pasture-based and housed dairy production systems in Great Britain - Brad P. Harrison; Martina Dorigo; Christopher K. Reynolds; Liam A. Sinclair; Ricard B. Tranter; Partha P. Ray (PLoS ONE, 2025)
Mitigating environmental phosphorus loading (EPL) from dairy farms reduces water pollution and improves the sustainability of production. Studies generally simulate EPL from dairy farms using a representative farm type from existing databases. However, housed and pasture-based dairy farming systems might contribute to eutrophication differently and have a varied feasibility of implementing mitigation. This study is the first that quantified EPL from dairy farms using data for FARMSCOPER collected from farmers and comparing EPL and identifying a least-cost suite of mitigation methods. Structural characteristics of 27 dairy farms in Great Britain (GB) were collected. Annual EPL from each farm was simulated in FARMSCOPER under three scenarios. Mean EPL of the production systems was compared to investigate any relationship between EPL and average 305 day adjusted milk yield of cows on each farm. A least-cost suite of mitigation methods was optimised for two model farms to represent either a housed or pasture-based system. Across both systems, ‘current’ implementation of mitigation methods was simulated to have reduced EPL from 0.63 to 0.56 kg P/ha (11%). The ‘current’ EPL positively correlated with milk production on a kg and kg/ha basis (P ≤  0.001 and P =  0.033, respectively). Farms operating a housed system had a mean ‘current’ EPL that was 59% greater than the pasture-based system though not significant (P =  0.316). This was partly due to a small sample size and because FARMSCOPER’s estimates exclude variations in farm practices (i.e., feeding). EPL was reduced by ~ 50% and ~ 60% without incurring annual financial losses by implementing existing mitigation methods for pasture-based and housed systems, respectively. This study highlights the importance of mitigating EPL from GB dairy farming, especially considering the increasing number of higher yielding herds and housed production systems. Furthermore, emphasis should be on increasing implementation of system-specific mitigating methods; efforts to include more recent and specific farm data to improve the FARMSCOPER tool will benefit this.